ANALISIS KAWASAN DESAIN DALAM PENINGKATAN KOMPETENSI MENDESAIN BAGI ANGGOTA UNIT DESAIN GRAFIS TEKNOLOGI PENDIDIKAN - Rahmani; Novrianti; Amsal, Mutiara Felicita; Alkadri Masnur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of the design domain in enhancing the design competencies of members of the Graphic Design Unit in the Educational Technology Study Program at Universitas Negeri Padang. This research employed a descriptive quantitative approach, with data collected through questionnaires distributed to all members of the Graphic Design Unit. The research variables consisted of the design domain, focusing on message design and learner characteristics, and design competency, which included work attitude, knowledge, skills, and creativity. The findings indicate that all indicators were categorized as high to very high. The message design indicator was classified as very high, with a mean score of 4.10 and a percentage of 82%. The learner characteristics indicator showed that students were able to integrate theory and practice and adapt designs to users’ needs, with a mean score of 3.92 and a percentage of 78.40%, which falls within the high category. Furthermore, students’ design competencies demonstrated substantial improvement, as reflected in their professional work attitude, which achieved a mean score of 4.23 and a percentage of 84.60%, categorized as very high. Technical skills mastery obtained a mean score of 3.99 and a percentage of 79.80%, categorized as high. In addition, creativity achieved a mean score of 4.21 and a percentage of 84.20%, which was categorized as very high. In conclusion, the design domain makes a significant contribution to improving students’ design competencies. The Graphic Design Unit, as an organizational platform, also plays a strategic role in supporting the comprehensive development of students’ skills in both academic and non-academic aspects.